2018
DOI: 10.3389/fpls.2018.01745
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure and Localization of Levan, the Predominant Fructan Type in Underground Systems of Gomphrena marginata (Amaranthaceae)

Abstract: Gomphrena marginata Seub. (Amaranthaceae) is an endemic species from Brazilian campos rupestres with a fructan accumulating underground reserve system. Analyses of high performance anion exchange chromatography (HPAEC–PAD) revealed the presence of the soluble carbohydrates glucose, fructose, sucrose, 1-kestose, 6-kestose, nystose and fructans with degree of polymerization (DP) up to approximately 40 fructose units. Data of 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy, including Heteronuclear Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…This could be due to the low amount/quantity of fructan produced by G. cerinus DSM 9533 T , which could not be detected. Moreover, chemical shifts of C2 and C6 which correspond to the β-(2–6)–linkages were in accordance with the controls and previous literature confirming the presence of levan [ 3 , 50 ].…”
Section: Resultssupporting
confidence: 90%
“…This could be due to the low amount/quantity of fructan produced by G. cerinus DSM 9533 T , which could not be detected. Moreover, chemical shifts of C2 and C6 which correspond to the β-(2–6)–linkages were in accordance with the controls and previous literature confirming the presence of levan [ 3 , 50 ].…”
Section: Resultssupporting
confidence: 90%
“…Moreover, β-(2→6) linkages make up 70% of the total linkages, while the remaining 30% represent β-(2→1) branches [77]. Since the initial molecule in BL formation is sucrose, either internal or terminal glucose moiety can be aperient as a by-product of BL biosynthesis by levansucrase (EC 2.4.1.10), responsible for the catalysis of sucrose [78]. A detailed profile of individual carbohydrates of BL is depicted in Figure 6 and Table 4.…”
Section: Compositional Analysis Of Bacterial Levan Produced By Strept...mentioning
confidence: 99%
“…They are mostly found in bacteria, and in few grass species including Dactylis glomerata. A recent study by Joaquim et al (2018) found that levan is the predominant fructan type in roots of Gomphrena marginata, a member of family Amaranthaceae. Levan-type fructans of bacterial origin are of high-molecular weight (DP 10 000-100 000) while those of plant origin are found to be short polymers of highly branched molecules (Roberfroid, 2004).…”
Section: Levan-type Fructansmentioning
confidence: 99%